Children's influence on family purchase decision in India. - Desai, Tanvi (2008)
The importance of children in purchase decision making has grown over the years. They not only make purchase decisions for personal consumption but they also influence family purchase decision-making (Kaur and Singh, 2006). This research looks at available literature, which is discussed with respect to children influence on product categories, decision-making stages, socialising agents like parents, peers and media and role of family communication in purchase decision making. Demographic variables like age and gender of the children reflect their purchase decision in the research. This study is particularly focussing on India. Indian literature gives a brief scenario of Indian culture and its impact on children purchase behaviour.